A Critical Review of Statement of Government Accounting Standard (SGAS) Regarding Accounting for Investment - Irwan Taufiq Ritonga (Universitas Muhammadiyah Yogyakarta, Indonesia, 2021)
Research aims: This article aims to provide a critical review of the Statement of Government Accounting Standard (SGAS) of Indonesia regarding Accounting for Investment (2016 Revision)Design/Methodology/Approach: This article is a critical review, which criticism seen from a philosophical and theoretical point of view.Research findings: There are five issues that need improvement so that SGAS Accounting for Investment becomes better. The five issues are the definition of government investment that is not in line with the vision of government organizations, inconsistency between investment definition and accounting treatment of investment proceeds, lack of comprehensive accounting treatment for negative investment value, inconsistency between investment definition and disclosure terms, inaccuracy of diction or grammar choice, and incomplete glossary.Theoretical contribution/Originality: the arguments presented in this article can be used by scholars who focus on government accounting to develop a theory of government accounting.Practitioner/Policy implication: Findings of this study can be inputs for the Government Accounting Standard Committee (GASC) to improve government accounting standards in Indonesia, especially SGAS of Accounting for Investment.